Non-linear circuit based model of PMSM under inter-turn fault: a simple approach based on healthy machine data - Belguerras, Lamia; Arellano-Padilla, Jesus; Arumugam, Puvaneswaran; Hamiti, Tahar; Mezani, Smail; Gerada, C. (Institution of Engineering and Technology, 2016)
The paper proposes a fast dynamic mathematical model to evaluate the performances of saturated permanent magnet synchronous machines (PMSM) under stator winding’s inter turn fault. The parameters of the model can be determined using only manufacturer’s data of the healthy machine. Two surface mounted PMSM have been considered to investigate the validity of the proposed approach; with distributed and concentrated winding. It has been shown that the proposed model predicts the fault current with a reasonable accuracy compared to the non-linear Finite Elements analyses and to the experimental results. This model can be incorporated in a global simulation environment of power electronic of electrical device since the computation time is very short.